Local Print Media Strategy to Maintain Market Existence in the Digital Era (Management of the “SUARA NTB” Newspaper in Lombok, West Nusa Tenggara) - Hafizni, Moh. (LEGAL BRIEF, 2024)
This study aims to determine the strategy used by the “SUARA NTB” newspaper to capture the market, maintain the local print media business, and determine the implementation of convergence. The study used a qualitative research methodology. The subjects of the study or informants were employees of the editorial staff of the “SUARA NTB” newspaper, who were selected based on purposive sampling techniques—data collection techniques through observation, interviews, and document searches. The results of this study indicate that the “SUARA NTB” newspaper has morphed from print media to online media, after previously producing content digitally. The “SUARA NTB” newspaper also applies media convergence or journalistic convergence to operate efficiently and maintain the increasingly competitive local media business in the digital era. The “SUARA NTB” newspaper expands its reader network by distributing content through digital or online media and social media by adopting the “The Long Tail” theory